2007
DOI: 10.4161/cc.6.6.3985
|View full text |Cite
|
Sign up to set email alerts
|

PKN Activation via Transforming Growth Factor-β1 (TGF-β1) Receptor Signaling Delays G2/M Phase Transition in Vascular Smooth Muscle Cells

Abstract: Previouisly published online as a Cell Cycle E-publication: http://www.landesbioscience.com/journals/cc/abstract.php?id=3985 Key woRDSPKN, TGF-β 1, smooth muscle, G 2 /M phase, cell cycle ACKnowleDGeMenTSWe thank Dr. Yoshitaka Ono for providing the PKN constructs. AbSTRACTThe transition of vascular smooth muscle cells (VSMCs) from G 2 phase into the M (mitosis) phase of the cell cycle is a tightly controlled process. As an arterial SMC prepares for a G 2 /M transition, the cell has primed the Cdc2/cyclinB1 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…De-phosphorylation of these negative regulatory sites is needed to activate the cdc2/cyclin B complex. Cdc25C is a major phosphatase that de-phosphorylates both sites on cdc2 to activate them (Su et al, 2007;Roshak et al, 2000). The decreased expression of cdc25C by TF treatment, as shown here, inhibited de-phosphorylation of cdc2 (Thr14 and Tyr15), resulting in inhibition of the cdc2/cyclin B complex formation.…”
Section: Discussionmentioning
confidence: 60%
“…De-phosphorylation of these negative regulatory sites is needed to activate the cdc2/cyclin B complex. Cdc25C is a major phosphatase that de-phosphorylates both sites on cdc2 to activate them (Su et al, 2007;Roshak et al, 2000). The decreased expression of cdc25C by TF treatment, as shown here, inhibited de-phosphorylation of cdc2 (Thr14 and Tyr15), resulting in inhibition of the cdc2/cyclin B complex formation.…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, in a follow-up study, PRK1 was found to specifically phosphorylate the related TRAF1, which lacks the JNK/IKK signaling effector domain but not its interactant TRAF2 or other TRAF members, leading to the recruitment of TRAF1 to the TNF receptor, silencing the receptor complex by PRK1 (55). Moreover, within the vasculature, PRK1 has been implicated in the mediation of VSM-specific gene expression promoting VSM differentiation, such as in response to transforming growth factor-␤1 (56,57). Keeping in mind the central role of TXA 2 within the vasculature, including the mediation of inflammatory disease, coupled with the finding herein of a direct interaction with and activation of PRK1, it will be of significant interest to investigate the possible interplay between those critical pathways, be it at the cellular or (patho)physiologic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Since the major regulator of G 2 to M transition is the M phase-promoting factor (MPF) [ 41,42], we proceeded by studying the effect of bromelain on this complex in terms of formation (via cdc2 and cyclin B1 levels) and phosphorylation status in A431 cells. Cdc25C is known as major phosphatase which dephosphorylates both sites of cdc2 to activate them [43,44]. We saw that cdc25C-phosphorylation (Ser198), normally required for its activation, was inhibited by bromelain which thereby curtailed the phosphorylation of cdc2 at Tyr15, inhibiting cdc2/cyclin B complex formation.…”
Section: Discussionmentioning
confidence: 87%